The influence of increased content of Ni(III) in NiFe LDH via Zn doping on electrochemical catalytic oxygen evolution reaction. (12th February 2023) - Zhou, Yan; Guo, Qianyu; Luo, Jiabing; Wang, Xingzhao; Sun, Fengchao; Wang, Chenchen; Wang, Shutao; Zhang, Jun
Abstract: Developing efficient oxygen evolution electrocatalysts always shows great importance in the field of electrolysis of water. In this work, Zn-doped NiFe LDH is synthesized via a facile hydrothermal reaction. A series of structural characterizations revealed that the doping of Zn into NiFe LDH lattice can cause lattice distortion, which facilitates the formation of active NiOOH layers. The Zn–NiFe LDH electrocatalyst shows excellent performance in electrocatalytic oxygen evolution reaction, even overbeat the state-of-art RuO2 . In addition, the doping of Zn into NiFe LDH significantly enhances the electrocatalytic stability of NiFe LDH, with only a 32.7 mV increase in potential after 100 h continuous OER electrolysis in 1.0 M KOH. The Zn–NiFe LDH provides an ideal strategy for designing highly efficient OER electrocatalysts for real applications. Highlights: NiFe LDH was successfully by Zn by a facile hydrothermal reaction. The doping of Zn induced phase transformation to NiFe LDH. The doping of Zn caused increment of Ni(III)/Ni(II) ratio in NiFe LDH. Zn-doped NiFe LDH showed high electrocatalytic activity and stability.